Comparison of the histopathological effects of two electrosurgical currents in an in vivo porcine model of esophageal endoscopic mucosal resection - Bahin, Farzan F.; Burgess, Nicholas G.; Kabir, Sharir; Mahajan, Hema; McLeod, Duncan; Subramanian, Vishnu; Pellise, Maria; Sonson, Rebecca; Bourke, Michael J. (Endoscopy, 2016)
Background and study aims: Stricture formation is the main limitation of endoscopic resection in the esophagus. The optimal electrosurgical current (ESC) for endoscopic resection in the esophagus and other gastrointestinal sites is unknown. There may be a relationship between the type of ESC used and the development of post-procedure esophageal stricture. Unlike the low power coagulating current (LPCC), the microprocessor-controlled current (MCC), which alternates between short pulse cutting and coagulation, avoids high peak voltages that are thought to result in deep thermal injury. The aim of this study was to determine the histopathological variables associated with these two commonly employed ESCs used for esophageal endoscopic resection.Methods: Standardized endoscopic resection of normal mucosa by band mucosectomy was performed by a single endoscopist in 12 adult pigs. The procedures were randomized 1 : 1 to either LPCC (ERBE 100 C at 25 W) or MCC (ERBE Endocut Q, Effect 3). Necropsy and esophagectomy were performed at 72 hours after the procedure. Two histopathologists, who were blinded to the ESC allocation, independently assessed the presence and depth of ulceration, necrosis and inflammation.Results: A total of 45 resections were analyzed. In the LPCC and MCC groups, ulceration extending into the muscularis propria was present in 9/24 (37.5 %) and 1/21 (4.8 %) resected specimens, respectively (P = 0.04). Necrosis extending into the muscularis propria was present in 13/24 (54.1 %) and 1/21 (4.8 %) resected specimens, respectively (P = 0.002). One case of microperforation with muscularis propria injury was noted in the LPCC group compared with none in the MCC group. The quantified mean depth of ulceration, necrosis, and acute inflammation was significantly greater in the LPCC group. Conclusions: In an in vivo porcine survival model of esophageal endoscopic mucosal resection, the use of MCC resulted in significantly less deep thermal ulceration, necrosis, and acute inflammation compared with LPCC. MCC should be used in preference over LPCC for esophageal endoscopic resection.